Impaired thyroid hormone receptor signaling in anterior hypothalamic parvalbumin neurons causes bradycardia in male mice - Beke Kolms; Riccardo Dore; Sarah C Sentis; Leonardo Vinicius Monteiro de Assis; Henrik Oster; Jens Mittag (European Thyroid Journal)
Thyroid hormone receptor α1 (TRα1) regulates body temperature and heart rate in humans and mice. In addition to its direct actions in target tissues, it also affects peripheral functions indirectly through the brain. While these central actions on peripheral tissues have been demonstrated for liver and brown fat, the consequences for cardiac functions are still enigmatic. Recently, a population of parvalbumin neurons has been discovered in the anterior hypothalamic area that depends on TRα1 for correct development and controls heart rate in a temperature-dependent manner. Here we test the hypothesis that not only developmental but also acute actions of TRα1 in hypothalamic parvalbumin neurons affect the central control of cardiovascular functions. We used an AAV-mediated stereotaxic approach to express a mutant TRα1R348C conditionally in hypothalamic parvalbumin cells, thus impairing TRα1 action specifically in these neurons. While this had no effect on metabolism or thermoregulation, using non-invasive radiotelemetry we observed a reduced heart rate both at 22°C and 30°C. Interestingly, heart rate was normalized when the animals were measured by ECG, which requires prior handling, suggesting that the impairment caused by the mutant TRα1 can be compensated in more stressful situations. Taken together, our data show that TRα1 signaling in hypothalamic parvalbumin neurons acutely affects the central control of heart rate, adding a novel mechanism to bradycardia in hypothyroidism. Furthermore, the data underline the importance of non-invasive recordings of in vivo functions in animal models with alterations in central thyroid hormone action.